Implementasi Metode Scrum–AHP dalam Mendukung Pengambilan Keputusan Pengembangan Produk Baru - Ahmad Nuryana; Yati Rohayati; Atya Nur Aisha (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The fast-moving consumer goods (FMCG) industry is facing rapid market changes so companies are required to accelerate the process of developing new products and improve the quality of decision-making. At PT XYZ, delays in backlog prioritization, cross-functional conflicts, and the lack of an objective prioritization mechanism caused several NPD projects to experience delays in launch. This study aims to identify the causes of backlog decision-making delays, determine cross-functional priority criteria, and design a Scrum-AHP-based backlog prioritization model in the FMCG industry. The research uses a sequential exploratory mixed method approach through interviews, focus group discussions, observations, and analysis of the Analytical Hierarchy Process (AHP) integrated with Scrum practice. The results show that project delays are mainly caused by priority conflicts between functions, repetitive revisions of needs, and unstructured prioritization processes. The research also produced five main priority criteria, namely market potential, technical feasibility, manufacturing readiness, investment requirement, and strategic alignment, with market potential as the highest weighted criterion. The implementation of the Scrum–AHP model has been proven to increase the transparency of backlog priorities, strengthen cross-functional collaboration, and accelerate the decision-making process in NPD activities. In addition, this model improves team coordination and reduces repetitive priority conflicts between departments. This study concludes that the Scrum–AHP model can support more effective and adaptive management of NPD in the FMCG industry while minimizing the risk of product launch delays.